2012
DOI: 10.1152/ajpheart.00833.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte deletion of mitofusin-1 leads to mitochondrial fragmentation and improves tolerance to ROS-induced mitochondrial dysfunction and cell death

Abstract: deletion of mitofusin-1 leads to mitochondrial fragmentation and improves tolerance to ROS-induced mitochondrial dysfunction and cell death. Am J Physiol Heart Circ Physiol 302: H167-H179, 2012. First published October 28, 2011 doi:10.1152/ajpheart.00833.2011.-Molecular studies examining the impact of mitochondrial morphology on the mammalian heart have previously focused on dynamin related protein-1 (Drp-1) and mitofusin-2 (Mfn-2), while the role of the other mitofusin isoform, Mfn-1, has remained largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
151
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(167 citation statements)
references
References 74 publications
15
151
0
1
Order By: Relevance
“…Consistent with this, a recent study reported that combined ablation of MFN1/ MFN2 in adult mouse heart results in fragmented mitochondria and decreased mitochondrial function, suggesting that mitochondrial fusion is essential for cardiac function (25). In contrast, cardiac MFN1 knock-out mice have normal cardiac function, although with smaller mitochondria; moreover, MFN1-deficient cardiomyocytes show improved viability in response to reactive oxygen species challenge (54). A recent study by Papanicolaou et al (26) reported that MFN2 depletion in the heart leads to modest myocyte hypertrophy, mild left ventricular dysfunction, and enlarged subsarcolemmal mitochondria with a lower mitochondrial membrane potential but normal respiration.…”
Section: Discussionmentioning
confidence: 60%
“…Consistent with this, a recent study reported that combined ablation of MFN1/ MFN2 in adult mouse heart results in fragmented mitochondria and decreased mitochondrial function, suggesting that mitochondrial fusion is essential for cardiac function (25). In contrast, cardiac MFN1 knock-out mice have normal cardiac function, although with smaller mitochondria; moreover, MFN1-deficient cardiomyocytes show improved viability in response to reactive oxygen species challenge (54). A recent study by Papanicolaou et al (26) reported that MFN2 depletion in the heart leads to modest myocyte hypertrophy, mild left ventricular dysfunction, and enlarged subsarcolemmal mitochondria with a lower mitochondrial membrane potential but normal respiration.…”
Section: Discussionmentioning
confidence: 60%
“…Mfn1 is an essential protein for mitochondria fusion events. Accordingly, decreased Mfn1 function has been shown to trigger a profound shift in the fusion/fission balance, toward a dramatically fragmented mitochondrial network in most, if not all, cells and tissues tested to date (Chen et al , 2003; Park et al , 2008; Papanicolaou et al , 2012; Dietrich et al , 2013; Kulkarni et al , 2016). Further, While Mfn1 mRNA levels did not compensate for Mfn2 loss, we observed that Mfn1 protein slightly decreased in the BAT and WAT form Mfn2‐adKO mice (Fig EV1A).…”
Section: Resultsmentioning
confidence: 99%
“…The sections were double stained with saturated 3% (w/v) uranyl acetate in 50% (v/v) alcohol and lead citrate; slides were then observed using a transmission electron microscope (Philips CM120, Eindhoven, The Netherlands). 22 Isolation and purification of Leydig cells Rats were anaesthetized using CO 2 and sacrificed by decapitation, and the testes were removed. The procedure for Leydig cell isolation was previously described.…”
Section: Electron Microscope Analysismentioning
confidence: 99%